Analysis of resource allocation and PM2.5 pollution control efficiency: Evidence from 112 Chinese cities - Yu Zhang (Elsevier, 2021)
The State Council of China initiated an air pollution prevention and control key (APPCK) city program to drive the national economic development and air pollution control since 2003. However, little known about whether the initiation is efficient. This paper examined the PM2.5 pollution control efficiency (PPCE) of 112 Chinese APPCK cities in 2003–2017 using Super-slack-based measure (Super-SBM) model with undesirable outputs. Results show that: (1) PPCEs of coastal cities (e.g., Shanghai, Guangzhou, and Suzhou) are much higher than those of less-developed northern cities (e.g., Jiaozuo, Anyang and Kaifeng); (2) the overall PPCE of 112 APPCK cities is relatively low and improvable; (3) the annual average growth rate of global Malmquist-Luenberger productivity index is 6.3%; (4) the technological progress is a significant contributor to improve the PPCE of these cities with 3.1% global technological change. These results provide reference to not only the policy-makers of China for synergies and tradeoffs between economic development and PM2.5 pollution control but also the studies on PM2.5 pollution control efficiency in the international context.